2018
DOI: 10.14740/jocmr3356w
|View full text |Cite
|
Sign up to set email alerts
|

The Celiac Trunk and Its Anatomical Variations: A Cadaveric Study

Abstract: BackgroundThe celiac artery, celiac axis or celiac trunk is the first major abdominal branch of the aorta. Anatomic variations and accessory vessels have been reported with variable percentages. The purpose of this study was to report the pattern of the celiac trunk and its anatomic variations in a sample of Mexican population.MethodsCeliac trunk dissection was performed in 140 fresh cadavers. Cadavers of Mexican subjects aged 18 years and older were included. Cadavers with previous upper abdominal surgery, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
2
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 26 publications
(52 reference statements)
7
35
2
5
Order By: Relevance
“…The most frequent vertebral levels of the CoT, SMA, IMA, and AB in our study population were T12 (53.48%), L1 (54.78%), L3 (63.19%), and L4 (66.96%), respectively, irrespective of the sex or age of the patient (0–19 years). This supports and extends on the results by Subramaniam et al () who also report the same vertebral levels as being the most frequent for children aged 0–11 years (frequency of 37–77%); and is consistent with the majority of adult studies reporting the vertebral level of the CoT (Mirjalili et al, ; Pinal‐Garcia et al, ), SMA, IMA (Mirjalili et al, ), and the AB (Kornreich et al, ; Chithriki et al, ; Lee et al, ; Mirjalili et al, ; Moussallem et al, ; Keskinoz et al, ). Despite these similarities in most frequent levels, these results emphasize the large variation in vertebral level expected in locating the splanchnic branches of the abdominal aorta where 46.52% of children in our study demonstrated a CoT level other than T12 (T11‐L1) and 45.22% of children demonstrated a superior mesenteric level other than L1 (T12‐L1/L2) (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The most frequent vertebral levels of the CoT, SMA, IMA, and AB in our study population were T12 (53.48%), L1 (54.78%), L3 (63.19%), and L4 (66.96%), respectively, irrespective of the sex or age of the patient (0–19 years). This supports and extends on the results by Subramaniam et al () who also report the same vertebral levels as being the most frequent for children aged 0–11 years (frequency of 37–77%); and is consistent with the majority of adult studies reporting the vertebral level of the CoT (Mirjalili et al, ; Pinal‐Garcia et al, ), SMA, IMA (Mirjalili et al, ), and the AB (Kornreich et al, ; Chithriki et al, ; Lee et al, ; Mirjalili et al, ; Moussallem et al, ; Keskinoz et al, ). Despite these similarities in most frequent levels, these results emphasize the large variation in vertebral level expected in locating the splanchnic branches of the abdominal aorta where 46.52% of children in our study demonstrated a CoT level other than T12 (T11‐L1) and 45.22% of children demonstrated a superior mesenteric level other than L1 (T12‐L1/L2) (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the typical splanchnic vessel vertebral levels reported in anatomy textbooks, recent studies in cadaveric dissection and CT angiography have demonstrated these frequent levels in adults may only constitute 34–48% of patients for the CoT (Yang et al, ; Mirjalili et al, ; Mu et al, ; Pinal‐Garcia et al, ) and 50–67% of patients for the AB (Kornreich et al, ; Chithriki et al, ; Pirro et al, ; Datta et al, ; Mirjalili et al, ; Moussallem et al, ; Keskinoz et al, ), with significant variation in vertebral levels between patients. Despite Subramaniam et al () reporting vertebral levels in children from 0 to 11 years of age, it is unclear whether the vertebral level of the splanchnic branches changes with age and whether sex differences exist in splanchnic position.…”
Section: Introductionmentioning
confidence: 99%
“…The CT, also known as the coelic artery, coelic axis or truncus coeliakus, usually arises just below the aortic hiatus at the level of the intervertebral disc between the T12 and L1 vertebrae. The CT is normally 1.5 to 2.3 cm long, and its trunk traverses horizontally forward, trifurcating into the LGA, CHA, and SA (55-100% of the population) [1,3,4,[6][7][8][9][10]12,14,16,18,[23][24][25][26]28,29,33,34,[39][40][41][42][43][44]. This trifurcation was first described by Haller in 1756 as tripus Halleri [7,8,18,21,22,24,28,30,35,45,46].…”
Section: Celiac Trunk Variationsmentioning
confidence: 99%
“…These branches form a continuous longitudinal anastomotic channel along the Branching pattern variations of the celiac trunk and superior mesenteric artery in a 72-year-old white female cadaver [45]. Pinal-Garcia et al (2018) found the origin of CT to range from the T10 vertebral body to the L1 vertebral body [28].…”
Section: Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation